Trabeculectomy Surgery in Primary and Secondary Glaucoma: Retrospective Cross-sectional Analysis - Christine, Reinne Natali; Tanong, Nicolas Dwiki; Rombe, Claudia Valoryn Iona; Angreni, Frisca (Journal of Applied Nursing and Health, 2025)
Background: Glaucoma remains a leading cause of permanent blindness worldwide, with elevated intraocular pressure (IOP) as the most modifiable risk factor. When medical therapy fails, trabeculectomy is often the preferred surgical option, though its effectiveness may differ based on the type of glaucoma. Primary glaucoma is typically idiopathic, while secondary glaucoma results from identifiable causes such as trauma, inflammation, or diabetes. Understanding these distinctions is essential for optimizing surgical outcomes and tailoring patient-specific treatment strategies. This study aims to determine whether there is a difference between the reduction in intraocular pressure in primary and secondary glaucoma after undergoing trabeculectomy surgery. Methods: This descriptive cross-sectional study used purposive sampling to select medical records of patients who underwent trabeculectomy at the Christian University of Indonesia Teaching Hospital from July 2021 to June 2022. A total of 30 patients were included. Inclusion criteria were patients diagnosed with either primary or secondary glaucoma who underwent trabeculectomy and had complete pre- and postoperative IOP data. Exclusion criteria included patients with previous glaucoma surgery, incomplete medical records, or less than one month of follow-up. The primary outcome was the percentage reduction in IOP one month postoperatively.. Results: The results showed that the percentage reduction in IOP within 1 month in primary glaucoma was 43.54%, whereas in secondary glaucoma, it was 41.87%. P value > 0.05 in all postoperative IOPs between primary glaucoma and secondary glaucoma. Conclusion: Trabeculectomy is still the first choice to reduce IOP, which has failed pharmacological treatments. However, there was no significant difference between decreased intraocular pressure in patients with primary and secondary glaucoma.